Exploring the Mechanisms and Strategies for Muscular Hypertrophy: Implications for Resistance Training and Performance Enhancement (GYMNASIUM, 2025)
Muscular hypertrophy, the process of muscle growth in response to resistance training stimuli, plays a crucial role in enhancing strength, athletic performance, and overall body composition. This research aims to delve into the mechanisms underlying muscularhypertrophy, examine effective strategies for optimizing muscle growth, and explore the practical implications of hypertrophy for individuals engaged in resistance training. By synthesizing relevant studies and research findings, this research seeks to provide insights into the science of muscle hypertrophy and its implications for exercise and performance enhancement. The way the body responds to muscle overload to gain muscle mass is still undergoing scientific investigation. In this sense, it is logical to examine contemporary understanding of muscular hypertrophy and to highlight some effective training approaches.
Keywords: athlete, fitness, muscle, mass grow, force